2016
DOI: 10.1111/jac.12179
|View full text |Cite
|
Sign up to set email alerts
|

Canopy Architecture and Leaf Nitrogen Distribution of Rice (Oryza sativa L.) under Chronic Soil Water Deficit

Abstract: The development of vertical gradients of specific leaf nitrogen (SLN) in accordance with light gradients within a canopy is important for maximising resource‐use efficiency. In this study, we aimed to clarify the effect of chronic soil water deficit on the SLN gradient in rice. In a series of field experiments, SLN gradients of an indica cultivar and a tropical japonica cultivar were investigated under chronic soil water deficit. As a result, SLN gradient of an indica cultivar tended to be more uniform than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Reduced resource allocation to elongating internodes during the reproductive stage led to less competition between organs for nonstructural carbohydrates, thereby enabling larger panicle size in semidwarf varieties (Kato et al., 2014). Simultaneously, the canopy structure of these varieties has been modified to lower the light extinction coefficient (i.e., by producing more upright leaves and tillers), which has contributed to greater biomass accumulation during the grain‐filling stage (Okami, Kato, & Yamagishi, 2016; Peng et al., 2008). However, breeders of short‐duration varieties should modify plant development to increase the current level of LAI during the limited period of vegetative growth.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced resource allocation to elongating internodes during the reproductive stage led to less competition between organs for nonstructural carbohydrates, thereby enabling larger panicle size in semidwarf varieties (Kato et al., 2014). Simultaneously, the canopy structure of these varieties has been modified to lower the light extinction coefficient (i.e., by producing more upright leaves and tillers), which has contributed to greater biomass accumulation during the grain‐filling stage (Okami, Kato, & Yamagishi, 2016; Peng et al., 2008). However, breeders of short‐duration varieties should modify plant development to increase the current level of LAI during the limited period of vegetative growth.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that WD may accelerate loss of leaf nitrogen and chlorophyll, and enhance senescence as it was observed in wheat (Yang et al, 2001 ). Recently, Okami et al ( 2016 ) observed that the optimal vertical distribution of leaf nitrogen content expressed on leaf mass basis, N m , may be affected by drought in an indica cultivar of rice. But generally it takes severe stress before the structure, not purely the functioning, of the photosynthetic machinery is affected.…”
Section: Damage Indicatorsmentioning
confidence: 99%
“…The potential photosynthetic capacity of rice leaf was highly related to leaf nitrogen content (Xu et al 2014, Yang et al 2016, and Vcmax, Jmax, and Vp markedly increased with an increasing leaf nitrogen content (Nakano et al 1997, Yin et al 2009, Gu et al 2012. Moreover, the leaf nitrogen content was low for the upper new-emerged and unexpanded leaf and usually decreased from the top to the bottom of rice canopy for the fully expanded leaf (Yang et al 2014, Okami et al 2016, which indicated the patterns of Vcmax, Jmax, and Vp in Fig. 3A-C.…”
Section: Discussionmentioning
confidence: 62%